Pieds et empreintes de pieds dans les cultes isiaques - Laetizia Puccio (Mélanges de la Casa de Velázquez, 2010)
Studies of Isaihanic cults in the Iberian Peninsula  have turned up a number of documents that depict a foot, as such or engraved on a votive stele, raising the question of the origin of this symbol. In the context of Egyptian gods, it symbolises wealth and abundance in the Pharaonic religion. The two models spread from the Nile valley throughout the Mediterranean world, reaching Hispania in the 2nd century, most certainly by way of the African continent. In the absence of any reference in ancient literature, the research that has been conducted into these depictions and the different variations on them does not warrant the attribution of a single meaning. Like the steles dedicated to Isis, Serapis feet most often embody divine epiphany, but they may also be seen as simple devotional symbols. When the footprints match those of the goddess and the steles are placed before the entrance to the temple, they could refer to a welcoming ritual.